Effect of a concomitant urologic procedure on outcomes following cytoreductive surgery with hyperthermic intraperitoneal chemotherapy. Issue 2 (18th January 2016) - Lyon, Timothy D.; Turner II, Robert M.; Nikonow, Tara N.; Wang, Li; Uy, Jamie; Ramalingam, Lekshmi; Holtzman, Matthew P.; Pingpank, James F.; Bartlett, David L.; Davies, Benjamin J.
Abstract : Background and Objectives: To evaluate whether urologic procedures during cytoreductive surgery with hyperthermic intraperitoneal chemotherapy (CRS‐HIPEC) are associated with adverse postoperative outcomes. Methods: We identified patients who underwent CRS‐HIPEC at our institution from 2001 to 2012 and compared outcomes between operations that did and did not include a urologic procedure. Results: A total of 938 CRS‐HIPEC procedures were performed, 71 of which included a urologic intervention. Urologic interventions were associated with longer operative times (547 vs. 459 min, P < 0.001) and greater length of stay (15 vs. 12 days, P = 0.003). Major complications (Clavien III and IV) were more common in the urologic group (31% vs. 20%, P = 0.028). On multivariable analysis, urologic procedures were associated with a low anterior resection (OR: 2.25, 95%CI 1.07–4.74, P = 0.033) and a greater number of enteric anastomoses (OR: 1.83, 95%CI 1.31–2.56, P < 0.001). At a median follow up of 17 months (IQR 5.6–35 months), addition of a urologic procedure did not significantly impact overall survival for appendiceal or colorectal cancers. Conclusion: Urologic surgery at the time of CRS‐HIPEC is associated with longer operative times, length of stay and increased risk of major complications, but not with decreased overall survival. J. Surg. Oncol. 2016;113:218–222 . © 2016 Wiley Periodicals, Inc.